Microalgae in novel food products - Sousa, Isabel (2010)
The implications of diet on health sustainability have assumed a major importance, supported by considerable epidemiological evidences, and is well recognized by the scientific community and general public, on developed countries. Microalgae are able to enhance the nutritional content of conventional food and feed preparation and hence to positively affect humans and animal health due to their original chemical composition, namely high protein content, with balanced amino acids pattern, carotenoids, fatty acids, vitamins, polysaccharides, sterols, phycobilins and other biologically active compounds, more efficiently than traditional crops. The aim of this chapter is to review the most important features of microalgae in animal and human nutrition, particularly in the development of novel design-foods rich in carotenoids and polyunsaturated fatty acids with antioxidant effect and other beneficial health properties.